Use of nonbarrier contraceptives among women with HIV - Paulsen, Fie W; Tetens, Malte M; Gerstoft, Jan; Kronborg, Gitte; Johansen, Isik S; Larsen, Carsten S; Wiese, Lothar; Dalager-Pedersen, Michael; Lunding, Suzanne; Nielsen, Lars N; Pinborg, Anja B; Weis, Nina; et al. (AIDS (London), 2025)
The aim of this study was to investigate the use of nonbarrier contraceptives among women with HIV (WWH) compared to women from the general population (WGP) in Denmark. A nationwide, population-based, matched cohort study. We included WWH aged 16-50 years, treated at an HIV specialized clinic, and included in The Danish HIV Cohort Study between 1995 and 2021 and an age-matched comparison cohort of WGP. We examined use of hormonal contraception, intrauterine devices (IUDs), and sterilization from 10 years before to 20 years after study inclusion. Additionally, we calculated age-standardized proportions and incidences over calendar time. We included 1720 WWH and 17 720 WGP. Median age was 33 years and almost half of WWH had African origin (41%). Nonbarrier contraceptive use was lower among WWH (8.5%) compared to WGP (32.1%) at study inclusion. Before and after inclusion, WWH had nearly half the nonbarrier contraceptive use of WGP, with notably lower hormonal contraception and IUD use. Initially, fewer WWH were sterilized, but 5 years after inclusion, sterilization became the preferred method among WWH. HC use increased among WWH after 2010 but decreased among WGP after 2005. IUD use increased among both groups during 1995-2021 but remained lower among WWH. Incidence of sterilizations remained stable in both groups. Use of nonbarrier contraceptives was lower among WWH compared to WGP. For WWH, sterilization became the preferred nonbarrier method few years after study inclusion. hormonal contraception and IUD use increased among WWH after 2010 but remained lower than for WGP. Improved contraceptive counseling is recommended to support reproductive health among WWH.